Grazing effects of goat-sheep mixes on vegetation structure and productivity of old fallow in the Sahel - Hiernaux, Pierre H.Y.; Fernández Rivera, S. (Society for Range Management, 1996)
In the short term, grazing of a 40-ha fallow in the Sahel, Niger, by sheep and goats reduced the standing herbage mass in the wet season and increased its disappearance during the dry season. The effects of stocking rate (62.5 or 125 k g liveweight/ha) and the proportion of sheep in the mixture (sheep:goat ratios of 0:6, 2:4, 4:2 and 6:0) varied from year to year. In the longer term, grazing also affected the botanical composition. Grasses were promoted at low grazing intensities and dicotyledons at high grazing intensities.